Ethical aspects of the profession of social worker - Jedynak, Witold (Social Welfare: Interdisciplinary Approach, 2014)
A set of moral standards plays an important role in social life, as it forms the basis for assessing the attitudes and behaviors of individuals. Ethics attempts to determine and resolve normative issues relating to the specific social situations. Thus provides a basis for establishing the rules of human functioning in the situation arising from a particular social or professional role. The purpose of this paper is to present some aspects of professional ethics of social workers affecting the standards of the profession. Secondary sources were used in preparation of this text, especially code of ethics of social workers and other axiological contents on the issues discussed. A social worker, whose activities are essentially social, performs many professional roles. Therefore, they should be guided by values and moral principles, arising from general ethics and specific standards contained in the code of ethics of the profession. Codified professional ethics helps a social worker in the proper performance of duties and is a reference point for resolving ethical dilemmas. Standards contained in the code of ethics uphold the dignity of the profession and at the same time indicate how the representatives of the profession should behave, and how they should not. The provisions of the code of ethics relate to the profession, relationships with coworkers, beneficiaries, employers and society. They include specific objectives and tasks of social work, understood as a practical human activity for people who need support and assistance in the fulfillment of basic needs and solving problems arising as a result of deprivation of those needs.